Świat przed Zagładą. Tajemnica istnienia archiwalnego obrazu filmowego we współczesnej strukturze filmowej na przykładzie filmu Po-lin. Okruchy pamięci Jolanty Dylewskiej - Kozłowski, Maciej (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
The World Before the Shoah: The Mystery of Archival Film Footage As Part of Contemporary Cinematic Structure Based on the Example of Jolanta Dylewska’s Po-Lin. Remains of Memory The text is an analysis of the composition of archival footage in contemporary documentary film. It presents artistic strategies concerning visual narration used in the film. From this perspective, it also describes the cinematic image of the provincial world of Jewish culture in Poland before II World War as captured by Jewish amateur cinematographers in their home movies, and how the same place is filmed nowadays. The mutual relationship between two visual layers is also interesting: archival footage and contemporary film and the meanings that arise as a result. Among the elements of visual film language are representations showing the metamorphosis of the place of action that occurred as a result of the passage of time and historical dramatic events. Also analyzed is the function of film close up in describing a wider context and portraits of witnesses who remember the world before the destruction of the Shoah.